Typo/graphic days 8 - Panayides, Angelos (My University, 2025)
The Lahti International Poster Triennial celebrated its 50th anniversary. Finland hosted 22nd international poster exhibition. June 6–September 7, 2025, Lahti Museum of Visual Arts Malva Opening ceremony June 5, 2025 The Lahti International Poster Triennial celebrated its 50th anniversary in 2025. Continuing a tradition that began in 1975, this graphic design competition and exhibition will now be held for the 22nd time in Lahti. To honour the triennial’s 50th jubilee, the theme of our special anniversary category will be ‘freedom of expression’. Although this inherent human right is protected in many countries, free speech still remains under threat in many parts of the world.
Keywords: triennial; exhibition; poster; catalogue